Agronomic performance of 'Cabernet Sauvignon' grapevine in altitude region on different rootstocks - Allebrandt, Ricardo (2025)
The objective of this work was to evaluate the effect of different rootstocks on the agronomic performance of the 'Cabernet Sauvignon' grapevine grown in the high-altitude region of Santa Catarina State. The rootstocks ‘Paulsen 1103’, ‘Courdec 3309’ and ‘101-14 Mgt’ were tested. The experiments were conducted in the municipalities of Painel (1,200 m) and São Joaquim (1,300 m), during the 2014/2015, 2015/2016 and 2016/2017 cycles. Yield components, vigor characteristics, cluster architecture and berry ripeness were evaluated. The rootstocks modified the yield and vegetative growth parameters. The rootstocks 1103P and 3309C presented the highest average yields per plant when compared to 101-14 Mgt. In the São Joaquim area (1,300 m), the rootstock ‘3309C’ had the highest number of clusters per shoot, the lowest leaf area/fruit ratio (cm² g-1) and the highest Ravaz index. The rootstock 101-14 Mgt reduced the size of Cabernet Sauvignon berries in Painel (1,200 m); and in São Joaquim (1,300 m), ‘101-14 Mgt’ and 3309C reduced the diameter and mass of the berries. The soluble solids and total acidity of Cabernet Sauvignon grapes suffered little influence from the rootstock in the two locations studied, throughout the cycles.